Business Model for Sustainable Development: An Insight from Malaysian Automotive Industry - Rashid, N.; Shami, S.A. (International Journal of Human and Technology Interaction (IJHaTI), 2018)
In the modern economy, doing business is a challenging task to overcome volatile competition from established firms in the local and global market. In order to attain sustainability, firms are advised to be ahead from the competitors in term of business model or in its management. In general, the Malaysian automotive industry performance is on a par with Thailand and holds the top three positions in the ASEAN car market due to the strong dominance of the domestic market. However, in the new millennia, the competition is no longer between the companies but about achieving economy, ecology and social sustainability. Thus, to stay competitive, the strategy shifted from profit orientation to the sustainable development. Therefore, this research aimed to provide empirical evidence about the critical success factors towards the achievement of company sustainability. This study employed a quantitative research methodology and 242 returned questionnaires were then analysed via Co variance-based SEM (CB-SEM). The outcome of this research emphasizes that technology collaboration, green human resource, eco culture and eco product innovation are important factors to meet the sustainability of Malaysian automotive industry, especially in economy, ecology and social development. This research is meaningful to attain the world wide and nation strategy to “Go Green.